Regioselective quinazoline C2 modifications through the azide–tetrazole tautomeric equilibrium - Līpiņš, Dāgs Dāvis; Jeminejs, Andris; Ušacka, Una; Mishnev, Anatoly; Turks, Māris; Novosjolova, Irina (Beilstein Journal of Organic Chemistry, 2024)
2-Chloro-4-sulfonylquinazolines undergo functional group swap when treated with an azide nucleophile: 1) the azide replaces the sulfonyl group at the C4 position; 2) the intrinsic azide–tetrazole tautomeric equilibrium directs the nucleofugal sulfinate from the first step to replace chloride at the C2 position. This transformation is effective with quinazolines bearing electron-rich substituents. Therefore, the title transformations are demonstrated on the 6,7-dimethoxyquinazoline core, which is present in pharmaceutically active substances. The methodology application is showcased by transforming the obtained 4-azido-6,7-dimethoxy-2-sulfonylquinazolines into the α1-adrenoceptor blockers terazosin and prazosin by further C2-selective SNAr reaction and azide reduction.
Keywords: aromatic nucleophilic substitution; azide–tetrazole equilibrium; 4-azido-2-sulfonylquinazolines; quinazolines; sulfonyl group dance